Blessing's bead - Edwardson, Debby Dahl (Farrar, Straus and Giroux, 2009)
In 1917, Aaluk leaves for Siberia while her sister Nutaaq remains in their Alaskan village and becomes one of the few survivors of an influenza epidemic, then in 1986, Nunaaq's great-granddaughter leaves her mother due to a different kind of sickness and returns to the village where they were born.